Excavated Margins: Notes on the Pondering of Matter in the Works of Ryoji Suzuki - Vladimir Krstic (Oz, 1999)
Ryoji Suzuki’s work defies definition. In spite of over twenty years of practice and a number of very important realizations which constitute landmarks in Japanese contemporary architecture, he has remained a person in the shadow created by the stylistic elusiveness of his own work.